Effects of pretreatments in convective dehydration of Rosehip (Rosa eglanteria) - Mabellini, Alejandra; Ohaco Dominguez, Elizabeth Haydee; Marquez, Carlos Alberto; De Michelis, Antonio; Lozano, Jorge Enrique (ISEKI Food Association, 2019)
The aim of this work was to experimentally determine drying curves for thin layer and bed drying of rosehip fruits, with and without pretreatments, to reduce processing times as a function of drying air operating variables, to propose dehydration kinetics of fruits and to determine its kinetic parameters for further use within drying simulation software. Fruits were pre-treated both chemically and mechanically, which included dipping the fruits in NaOH and ethyl oleate solutions; and cutting or perforating the fruit cuticle, respectively. Simulation models were then adopted to fit the kinetics drying data considering fruit volume shrinkage. These simple models minimized the calculation time during the simulation of deep-bed driers. Results show that pre-treatments reduced processing times up to 57%, and evaluated models satisfactorily predicted the drying of rosehip fruit. Effective mass diffusion coefficients were up to 4-fold greater when fruit was submitted to mechanical pretreatments.